TWO DIMENSIONAL CHROMATOGRAPHIC ANALYSIS AS A QUALITY MEASURE OF HERBAL EXTRACTS – SALVIA OFFICINALIS - Scheepmaker, Mandé Michelle; Gower, Neil Travis (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Homoeopathic mother tinctures and herbal extracts are used worldwide for medicinal purposes on the basis that the plant extractcontains the active components essential for medicinal use. Quality analysis of samples ensures that the correct active components are presentfor medicinal use. Thin layer chromatography has been used extensively to determine the quality of plant extracts and could just as readily beapplied to the assessment of quality of homoeopathic mother tinctures. The development of a multidimensional technique allows for greaterquality analyses of these extracts.Materials and Methods: The Salvia officinalis sample was extracted and the one dimensional thin layer chromatographic plate development ofextracted sample was performed according to the German Homoeopathic Pharmacopoeia (GHP). Before the two dimensional thin layerchromatographic plates where run, different solvent systems were tested through a comparison of the resultant one dimensional thin layerchromatographic plates with that of the plate developed according to the GHP. The two dimensional thin layer chromatographic plate wasdeveloped in one direction using the eluent given in the GHP, the plate was then rotated 90 degrees and further developed using neatdichloromethane.Results and Conclusion: The two dimensional thin layer chromatogram for the selected sample Salvia officinalis was successfully established.This results in a more extensive profile regarding the identification of the individual components present in the homoeopathic mother tincture.The further production of two dimensional chromatograms is essential to the expanded detailed analysis of individual products and potential rawmaterial production of even higher standards.